Consistent cytotoxic-T-lymphocyte targeting of immunodominant regions in human immunodeficiency virus across multiple ethnicities. - Frahm, N; Korber, B; Adams, C; Szinger, J; Draenert, R; Addo, M; Feeney, M; Yusim, K; Sango, K; Brown, N; SenGupta, D; Piechocka-Trocha, A; et al. (2004)
Although there is increasing evidence that virus-specific cytotoxic-T-lymphocyte (CTL) responses play an important role in the control of human immunodeficiency virus (HIV) replication in vivo, only scarce CTL data are available for the ethnic populations currently most affected by the epidemic. In this study, we examined the CD8(+)-T-cell responses in African-American, Caucasian, Hispanic, and Caribbean populations in which clade B virus dominates and analyzed the potential factors influencing immune recognition. Total HIV-specific CD8(+)-T-cell responses were determined by enzyme-linked immunospot assays in 150 HIV-infected individuals by using a clade B consensus sequence peptide set spanning all HIV proteins. A total of 88% of the 410 tested peptides were recognized, and Nef- and Gag-specific responses dominated the total response for each ethnicity in terms of both breadth and magnitude. Three dominantly targeted regions within these proteins that were recognized by >90% of individuals in each ethnicity were identified. Overall, the total breadth and magnitude of CD8(+)-T-cell responses correlated with individuals' CD4 counts but not with viral loads. The frequency of recognition for each peptide was highly correlated with the relative conservation of the peptide sequence, the presence of predicted immunoproteasomal cleavage sites within the C-terminal half of the peptide, and a reduced frequency of amino acids that impair binding of optimal epitopes to the restricting class I molecules. The present study thus identifies factors that contribute to the immunogenicity of these highly targeted and relatively conserved sequences in HIV that may represent promising vaccine candidates for ethnically heterogeneous populations.